Antecedents of online shopping behaviour: the moderating role of gender in Gauteng - Sikhalela, Khanyisa (My University, 2022)
Online shopping is a growing phenomenon, and, with the COVID19 pandemic, it has been exacerbated. This study sought to assess the antecedents of online shopping behaviour and the moderating role of gender. Driven by the need to expand the knowledge of digital marketing and consumer behaviour, research on consumer behaviour and gender was imperative. This study was motivated by the lack of studies in the South African context that have investigated the online shopping antecedents and how the relationship between these antecedents and online shopping is influenced by gender. To achieve the aim of the study, this study utilised a selfadministered questionnaire to collect data from 200 online shoppers from Gauteng province, South Africa. Correlation and regression analyses were used to evaluate the objectives of the study. Thus, a causal-comparative research design was employed to investigate the effect of perceived benefit, online consumer attitude, perceived risk and trust on online shopping, and how gender influences these relationships. The study revealed that perceived benefit, trust, and online consumer attitude positively affect online shopping. Perceived risk was found to have a negative effect on online shopping. Further results revealed that gender influences the relationships between online shopping behaviour and its antecedents. The study concluded that gender matters regarding online shopping behaviours in Gauteng province. It was recommended that online businesses implement gender-sensitive marketing strategies to attract more online buyers. The results imply that online businesses should pay attention to the four antecedents of online shopping to increase their online sales. Building trust and reducing the perceived risks would enhance online business growth. This suggests that gender-specific or gender-sensitive marketing strategies should be implemented to increase online shopping.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Gender; Online shopping; Perceived benefit; UCTD; SDG-8: Decent work and economic growth; SDG-5: Gender equality